Komparasi Performa Insulasi Termal Antara Dinding Batu Bata dan Batu Bata dengan Penambahan Insulasi Alang-Alang - Niniek Pratiwi; Baharuddin Hamzah; Rosady Mulyadi (Jurnal Teknik, 2020)
Buildings consume about 40% of the world's energy, beginning from the process of making the building itself to how the building could meet human thermal comfort needs. In the past, reeds were often used in traditional buildings, but unfortunately these days the practice is being abandoned. Several studies have shown that weeds can reduce building temperatures. However, these studies research has not examined how reeds are used as insulation material along with bricks so the purpose of this study is to compare the thermal insulation performance between plain brick and brick wall with the addition of reed insulation. The method used in this research is to use Ecotect simulation. Based on the results of simulations carried out it is known that model 1, namely the plain brick wall, has an outside-inside temperature difference of -1.32917 ° C. This means that the average temperature inside is hotter than the outside temperature by 1.32917 ° C. Meanwhile in model 2, the brick wall with the addition of reeds insulation has an outside-inside temperature difference of 0.445833 ° C. This means that the average temperature inside is cooler than the outside temperature by 0.445833 ° C. Therefore, it can be concluded that reeds could be used as thermal insulation material because it could store heat better than the material in Model 1, which is a plain brick wall.